Measurement of I-V and P-V Characteristics of Solar Panels Under Partial Shading Conditions - Hanif Hazman; Asnil Asnil (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2022)
Some factors that affect the solar panels in producing electrical energy are temperature and temperature, another important point is the shadows that block the sunlight to reach the surface of the solar panels. This study aims to analyze the characteristics of the solar panel configuration with various levels of shadows that block the sunlight. The method used is a simulation of the current and voltage characteristics produced by several solar panel configurations. The configurations used are Series Parallel (SP), Total Cross Tied (TCT), Triple Tied (TT), Bridge Link (BL) and Honey Comb (HC). The results showed that the electrical energy generated by the SP, TCT, TT, BL and HC configurations respectively were 501.9 W, 517.5 W, 508.1W, 502.5W, 507.2W. Thus it is known that TCT has the maximum results. Beberapa faktor yang mempengaruhi efisiensi dari panel surya untuk menghasilkan energi listrik adalah suhu dan temperature, factor lain yaitu bayangan yang menghalangi sinar matahari. Penelitian ini bertujuan untuk melihat karakteristik dari konfigurasi pemasangan panel surya dengan berbagai tingkat bayangan yang terjadi. Metode yang digunakan adalah simulasi karakteristik arus dan tegangan yang dihasilkan oleh beberapa konfigurasi panel surya. Konfigurasi yang digunakan yaitu Series Parallel(SP), Total Cross Tied (TCT), Triple Tied (TT), Bridge Link (BL) dan Honey Comb (HC). Hasil penelitian menunjukkan energi listrik yang dihasilkan pada konfigurasi SP, TCT, TT, BL dan HC secara berurut adalah 501.9 W, 517.5 W, 508.1W, 502.5W, 507.2W. Dengan demikian TCT memiliki hasil yang paling baik.